The challenge of generation gap within organization - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Ramli, Zalikha (IDOSI Publications, 2017)
Organizations are facing the retirement of many older workers and the challenge of recruiting and retaining young talent. However, few studies have empirically substantiated generational differences in work values.The differences generation representing Silent, Traditional or Veterans Generation, Baby Boomers, Generation X (Gen X) and Generation Y (Gen Me, also known as gen Y, or Millennials). Each generation is shaped by economic, social, historical and contemporary politics.This will create a conflict of generation gap in an organization that requires immediate action from the management and the workers themselves between which can be done to address this problem is to understand the nature and the characteristics of each generation in order to reduce the existing public perception of every generation and introduce appropriate measures to be taken by the management of the organization. Each generation and their unique perspective should be acknowledged and incorporated through the implementation of organizational policies